Cabaran Penerapan Sistem Penggajian Berasaskan Merit di Sektor Publik: Analisis Sistem Saraan Baru (SSB) di Malaysia - bin Embi, Muhamad Ali (TINGKAP, 2010)
ABSTRACT Merit pay has been widely used as a method of compensation in the public sector since the early 1980’s.  Malaysia’s merit pay system, known as the New Remuneration System (NRS), was implemented in 1992.  However, a growing body of research indicates numerous problems in the implementation of merit pay systems.  Any merit pay system, an OECD (Organisation for Economic Co-operation and Development) study suggests, needs to be carefully evaluated for its effect on the motivation of public servants.  This study attempts to assess the impact of the NRS on the motivation of Malaysian public servants. The results show that the NRS failed to satisfy key requirements for the effectiveness of merit pay and thus failed to motivate a majority of public servants.  The major problems include lack of confidence in the NRS, inadequate information and understanding of the system, ineffective goal-setting, unsatisfactory performance appraisal, lack of a clear link between performance and reward, and unfair distribution of reward. Kata Kunci: Sistem Saraan Baru (SSB), Sistem Merit, Sistem Penggajian, Kakitangan Awam, Ganjaran, Prestasi Kerja